The Main Directions of Construction of Red Army in Days of the Great Patriotic War - N. M. Vasilyev (Vestnik MGIMO-Universiteta)
The current situation in the world draws public attention to the problems of building the armed forces and keeping their readiness to provide defense and security of the country. Rigid centralization of military construction in such collective bodies as the State Defense Committee, the General Headquarters of the Supreme Commander, determination and meticulous work of folk commissioners and the General Staff to identify areas of building and resource mobilization for the implementation of decisions taken can serve as a guide for solving similar problems in our days. Balanced development of the armed forces, technical equipment of modern weapons, timely replacement of losses, creation and transfer of reserves, training in a rigid time limit - it is not a complete list of the problems of military development, which made the success and victory in the war possible. On the eve of the 70th anniversary of the Soviet victory in this war it is not only important not to forget about the titanic work done, dedication and heroism of the older generation of our compatriots, the generation of victors, but also to reflect on the acute problems of the present, in order to be worthy of the glory of our ancestors and preserve their honor to future generations of Russians.